The Effectiveness of Mindfulness-Based Cognitive Therapy Counseling to Improve the Psychological Capital and Academic Performance of Students with Nomophobia Symptoms at SMP Negeri 1 Arjawinangun - Sholihah, Farhatus; Eddy Wibowo, Mungin; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2023)
Psychological capital and academic performance are factors which drive nomophobia among students. This phobia can happen due to the lack of psychological capital and academic performance as well as because some impacts on emotion, behavior, and negative behavior. Therefore, mindfulness-based cognitive individual counseling was chosen to improve psychological capital and academic performance so that nomophobia can be reduced, and students can have good responsibility as a student. This study used an experimental method with a randomized pretest-posttest control group design and involved 10 eighth grade students at SMP Negeri 1 Arjawinangun as the subjects which were divided into two groups, namely one experimental group and one control group. Their data were analyzed using MANOVA. Once the data were analyzed, the mindfulness-based cognitive individual counseling could significantly improve the psychological capital and academic performance of the students with nomophobia symptoms with a sig. = 0.000< sig.= 0.05. This shows that the experimental group which received this counseling got better results than the control group.